1977
DOI: 10.1111/j.1600-0447.1977.tb03560.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulins, psychopathology and prognosis in schizophrenia

Abstract: On admission, IgA, IgG and IgM concentrations were determined in 76 schizophrenics, and the correlations of these concentrations to the variables relating to psychopathology, background and prognosis were investigated in the present study, which is a part of a more extensive unpublished study. On the basis of factorization, the highest IgM concentrations were found in withdrawn schizophrenics and the lowest in paranoid schizophrenics. Of the background variables, the patient's present age had a positive correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

1980
1980
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 19 publications
2
7
0
Order By: Relevance
“…One can only hypothesize as to why exceedingly high IgA levels are correlated with a favourable prognosis. Higher age at onset of illness is associated with higher than average IgA concentrations (5). Similarly in this study, the age at onset was higher in the group with exceedingly high IgA levels than in the control group.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…One can only hypothesize as to why exceedingly high IgA levels are correlated with a favourable prognosis. Higher age at onset of illness is associated with higher than average IgA concentrations (5). Similarly in this study, the age at onset was higher in the group with exceedingly high IgA levels than in the control group.…”
Section: Discussionsupporting
confidence: 81%
“…A higher than average IgA concentration, on the basis of the correlation coefficient, on initial admission indicated a less need for hospital care during the follow-up, which supports the earlier observations on the correlation between immunoglobulins and prognosis (5). The scattering diagram, however, indicates that the linear correlation coefficient does not adequately explain this relationship.…”
Section: Discussionsupporting
confidence: 65%
“…The low levels of IgG and IgG1 observed here can mark the stable phase of the disease and/or related to the duration of the disease. For example, in SZ during acute crisis and also depending upon the duration of the disease, an increase in the mean serum level of total IgG was observed [ 1 , 3 , 6 , 10 , 11 , 27 , 29 , 32 ]. In the present study, as the low levels of IgG and IgG1 persisted in the BD group when the duration of the disease is taken into consideration, One may hypothesize that at stable phase, the inflammatory processes might be less vigorous than in acute phase of established infection, say T. gondii or other intercurrent infections from environmental sources may contribute to such inflammatory flare up in BD and SZ.…”
Section: Discussionmentioning
confidence: 99%
“…Yet another report described a decreased IgD levels in BD [ 35 ]. Studies focusing on SZ revealed an elevation of IgA, IgM or IgG in the patients’ sera or CSF during acute phases of the disease ([ 1 , 3 , 6 , 10 , 11 , 16 , 27 , 29 , 32 ]). Interestingly, in SZ, IgG raises gradually to reach a peak at about 12 to 17 years after the onset typically mirroring persistence of an underlying infection [ 10 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…Abramsky and Litvin (1978) and again Knight (1982) postulated that antidopamine receptor antibodies might be the cause of schizophrenia. Several other studies reported changes in blood and CSF immunoglobulin levels of schizophrenic patients (Solomon et al, 1969;Strahilevitz et al, 1970Strahilevitz et al, , 1976Pulkkinen, 1977;de Lisi et al, 1981;Ahokas et al, 1985;Legros et al, 1985).…”
Section: Introductionmentioning
confidence: 95%